Zpracování meteorologických dat - Čmiel, Vratislav; Provazník, Valentine; Rozman, Jiří (International Society for Science and Engineering, o.s., 2008)
The paper describes basics of processing of the meteorological data which come from the meteorological station FAST VUT and the data processing software that was made for this purpose.

Článek seznamuje se základy zpracování meteorologických dat pořízených meteostanicí FAST VUT a s vytvořeným programovým vybavením k tomuto účelu.
The Meteorological Data Processing
Keywords: meteorologie; zpracování dat; větrná růžice; relativní vlhkost; teplota; databáze; sql; c++ builder; meteorology; data processing; wind rose; relative humidity; temperature; database; sql; c++ builder